Re-evaluating Pleistocene–Holocene occupation of cave sites in north-west Thailand: new radiocarbon and luminescence dating. (April 2022) - Conrad, Cyler; Shoocongdej, Rasmi; Marwick, Ben; White, Joyce C.; Thongcharoenchaikit, Cholawit; Higham, Charles; Feathers, James K.; Tumpeesuwan, Sakboworn; Castillo, Cristina C.; Fuller, Dorian Q.; Jones, Emily Lena
Abstract: Abstract : Established chronologies indicate a long-term 'Hoabinhian' hunter-gatherer occupation of Mainland Southeast Asia during the Terminal Pleistocene to Mid-Holocene (45 000–3000 years ago). Here, the authors re-examine the 'Hoabinhian' sequence from north-west Thailand using new radiocarbon and luminescence data from Spirit Cave, Steep Cliff Cave and Banyan Valley Cave. The results indicate that hunter-gatherers exploited this ecologically diverse region throughout the Terminal Pleistocene and the Pleistocene–Holocene transition, and into the period during which agricultural lifeways emerged in the Holocene. Hunter-gatherers did not abandon this highland region of Thailand during periods of environmental and socioeconomic change.